Madheshi Women and Feminist Movement in Nepal - Yadav, Ranju (Nepal Journal of Multidisciplinary Research, 2024)
Background: The formal feminist movement in Madhesh emerged in reaction to the discriminatory, oppressive, and autocratic actions perpetrated by the state, entwined with concurrent political movements, effectively spotlighting and confronting prevalent social issues. Feminist movements in Nepal have played a significant role in bringing about major changes in various aspects of society, advocating for gender equality, women's rights, and social justice. Methods: This research adopted a qualitative method with an intersectionality theoretical framework to explore the firsthand experiences of Madheshi women who have actively engaged in feminist movements. The research collected data from face-to-face in-depth interviews with 28 women political leaders, 8 women journalists, 15 women rights activists, and 3 family members of women rights activists and political leaders with purposive sampling. Similarly, this study also gathered the perceptions of 14 Madheshi men from various sectors. Results: This paper explores Madheshi women’s contribution to feminist and other movements in Nepal. It examines the challenges that they faced during the movements. The study underscores the heterogeneous nature of Madheshi women's involvement, illustrating varied roles across historical contexts. The findings of the study revealed that Madheshi women are challenging patriarchies through various means. Conclusion: There is a significant gap in the documentation of the Madheshi women's and feminist movements in Nepal. Despite their active participation in feminist movements, their voices and concerns persistently remain on the periphery. Novelty: The research documents the contribution, challenges, and strategies of Madheshi women adopted by Madheshi women. It also addresses the gap in the existing literature regarding the Madheshi women.